2009
DOI: 10.1179/175158309x12560424605150
|View full text |Cite
|
Sign up to set email alerts
|

Wear behaviour ofin situCu–Al2O3composites produced by internal oxidation of as cast alloys

Abstract: In the present study, the wear behaviour of Cu-Al 2 O 3 composites and Cu-Al alloys has been investigated. The experiment involved casting of Cu-Al alloys with 0?37, 1, 2 and 3 wt-% of aluminium under inert gas atmosphere. The composites were produced by internal oxidation of alloys at 950uC for 10 h in presence of Fe 2 O 3 and Al 2 O 3 powders mixture. The microstructures of composites were studied using SEM and atomic force microscopy. To identify wear behaviour of specimens, dry sliding pin-on-disk wear tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…An increase in microhardness has been observed with the increasing size of ZrSiO 4 but the wear rate also increases with increasing the size of ZrSiO 4 particle [4]. Peterson et al [16] and Purazrang et al [17] investigated the high-temperature solid-lubrication performance of several metal oxides and found that few metal oxides exhibit low friction behaviour at elevated temperatures. Kumar et al [12] investigated the relationship between the oxidation behaviour and tribological performance of the composites at high temperatures showing that the wear performance improved with the decreased particle size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in microhardness has been observed with the increasing size of ZrSiO 4 but the wear rate also increases with increasing the size of ZrSiO 4 particle [4]. Peterson et al [16] and Purazrang et al [17] investigated the high-temperature solid-lubrication performance of several metal oxides and found that few metal oxides exhibit low friction behaviour at elevated temperatures. Kumar et al [12] investigated the relationship between the oxidation behaviour and tribological performance of the composites at high temperatures showing that the wear performance improved with the decreased particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Tribological studies of AMCs with different nature, sizes and amounts of reinforcements on various Al-Si alloys are available in the literature [12][13][14][15][16][17][18]. However, the reported research work on the non-lubricated dry sliding wear performance of LM27 alloy with fine and coarse sized SiC P reinforced is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Cu-Al 2 O 3 composites are mostly used in electrode materials, especially spot welding [24,[29][30][31][32][33]. These composites are ordinarily prepared by conventional powder metallurgy [34] or casting [35] routes. However, the in-situ reinforced Al 2 O 3 can increase the strength and improve composites' tribological, electrical and thermal properties [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%